Severity of Covid-19 infection among kidney transplant recipients in Duhok city, Kurdistan region, Iraq - Saleem, Zana Sidiq Mohammed (Journal of Contemporary Medical Sciences, 2022)
Objectives: Kidney transplant recipients are risky group population in whom greater morbidity and mortality reported in comparison to general population. Methods: We examined a prospectively cohort of 80 SOT Kidney transplant recipients with first-wave COVID-19, participants assessed and grouped into severe and non-severe illness. Results: Eighty kidney transplant recipients involved in our study, with average age of 46.6 ± 12.2 years and kidney transplant duration of 6.4 ± 3.5 years. Fifty four were male (67.5%). Comorbidities included hypertension (60%), diabetes mellitus (18.8), coronary heart disease (3.8), and hypothyroidisim (2.5). Twelve patients had severe Covid-19 infection (15%) and sixty eight with non-severe (85%). Risk factors for severe COVID-19 infection in this study were male gender, old age, comorbidities, obesity, longer duration of COVID-19 symptoms, kidney transplantation duration, C-reactive protein > 24 mg/L, Interlukine-6 > 26pg/mL and D-Dimer level> 1000ng/mL Modulation of immunosuppressive drugs done only for severe cases Eight transplant recipients needed admission to hospital and one necessitate mechanical ventilation. Conclusion: Kidney transplant recipients are at high risk of acquiring opportunistic infections including COVID-19 infection. The most important strategy in kidney transplant recipients to prevent COVID-19 infection is through adopting preventive measures in particular the use of masks and avoidance of crowded non-ventilated places. Risk stratification and poor outcome factor is crucial strategy to prevent spread of the infection.